Selexipag for the treatment of connective tissue disease-associated pulmonary arterial hypertension. Issue 2 (17th August 2017) - Gaine, Sean; Chin, Kelly; Coghlan, Gerry; Channick, Richard; Di Scala, Lilla; Galiè, Nazzareno; Ghofrani, Hossein-Ardeschir; Lang, Irene M.; McLaughlin, Vallerie; Preiss, Ralph; Rubin, Lewis J.; Simonneau, Gérald; et al.
Patients with connective tissue disease-associated pulmonary arterial hypertension (PAH-CTD) have a poor prognosis compared with other aetiologies. The underlying CTD can influence treatment response and outcomes. We characterised the GRIPHON study PAH-CTD subgroup and evaluated response to selexipag. Of 334 patients with PAH-CTD, PAH was associated with systemic sclerosis (PAH-SSc) in 170, systemic lupus erythematosus (PAH-SLE) in 82 and mixed CTD/CTD-other in 82. For the primary composite endpoint of morbidity/mortality, hazard ratios (HR) and 95% CI were calculated using Cox proportional hazard models. Compared with the overall GRIPHON population, the CTD subgroup was slightly older with a greater proportion of females and shorter time since diagnosis. Patients with PAH-SSc appeared to be more impaired at baseline, with a more progressive disease course. The converse was observed for PAH-SLE. Selexipag reduced the risk of composite morbidity/mortality events in patients with PAH-CTD by 41% (HR 0.59; 95% CI 0.41–0.85). Treatment effect was consistent irrespective of baseline PAH therapy or CTD subtype (interaction p=0.87 and 0.89, respectively). Adverse events were predominately prostacyclin-related and known for selexipag treatment. GRIPHON has allowed the comprehensive characterisation of patients with PAH-CTD. Selexipag delayed progression of PAH and was well-tolerated among PAH-CTD patients, including those with PAH-SSc and PAH-SLE. Selexipag delays disease progression and is well tolerated in PAH-CTD, irrespective of subtype or other PAH therapy http://ow.ly/SvIV30cqo9J